Les Sept Douleurs de la Sainte Vierge, Meditations, Reflexions, Prieres - Liguori, Alphonse de (Desclee, De Brouwer & Cie, 1893)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm